Microwave-assisted synthesis of rod-like CuO/TiO2 for high-efficiency photocatalytic hydrogen evolution. (14th December 2015) - Yu, Yi-Hsien; Chen, Ying-Pin; Cheng, Zhengdong
Abstract: CuO-deposited TiO2 rod composites were prepared through a microwave-assisted green method for high efficiency hydrogen evolution. The porous CuO/TiO2 rods with crystallinity and high specific surface (249.1 m 2 /g) area were obtained as-synthesized without calcination. Hydrogen yields were proved to be significantly improved with appropriate amount of CuO deposited onto TiO2 rods. The improved photocatalytic performance was attributed to the synergistic effects of high surface area, specific energy band structure, and enhanced light harvesting at the interface of CuO and porous TiO2 rods. Graphical abstract: Highlights: CuO/TiO2 rods were prepared from a green and rapid microwave-assisted method. Porous structure of the material provides with high surface area for H2 evolution. CuO deposition improves charge transfer and stability of the material.